Ending Cervical Cancer Screening in Low-Risk Women After Age 65 - Emily Boone; Michael Karp; LaVonna Lewis (SAGE Publishing, 2018)
Background: Current evidence-based cervical cancer testing guidelines recommend that screening of low-risk women ceases after age 65. Despite this, research suggests that continued testing by primary care providers remains common and represents unnecessary patient discomfort, cost, and consumption of valuable primary care resources. Objective: To understand why primary care providers might knowingly ignore consensus evidence-based screening guidelines for cervical cancer in low-risk women of this age-group and to identify barriers to adherence with best practice recommendations. Methods: A survey tool to identify barriers to adherence with current guidelines for cervical cancer screening in low-risk women older than age 65 was mailed to 4929 randomly selected primary care providers throughout California. Providers were asked to indicate the predominant reason(s) they might knowingly continue cervical cancer screening in women older than 65 years, despite evidence-based recommendations to the contrary. Results: Qualified surveys were received from 1259 (25.5%) of those surveyed, representing primary care providers of all types, practicing in areas of vastly different demographics. Despite published reassurance to the contrary, many providers retain fear that discontinuation of testing in low-risk women after age 65 may result in missed invasive cervical cancer. Even among health-care providers who agree that cessation of screening is safe, other circumstances prompt their recommendation to continue cervical screening. Conclusion: Although the data from this study suggest areas of policy intervention to lessen unnecessary cervical cancer screening, the broader implication is that advancement of evidence-based medicine will be of little value in improving the quality and cost of health care if barriers to guideline adherence are poorly understood and addressed.